A comparative investigation of the corrosion and tribocorrosion behaviour of nitrocarburized, gas nitrided, fluidized-bed nitrided, and plasma nitrided plastic mould steel - Boztepe, E.; Alves, A. C.; Ariza, E.; Rocha, L. A. [UNESP]; Cansever, N.; Toptan, F. (Elsevier, 2018)
The present study aims to compare the corrosion and tribocorrosion behaviour of nitrocarburized, gas-nitrided, fluidized-bed nitrided, and plasma-nitrided Impax Supreme (equivalent to AISI P20) pre-hardened plastic mould steel. Corrosion behaviour was investigated by electrochemical impedance spectroscopy and potentiodynamic polarization in 3.5 wt% NaCl solution. Tribocorrosion tests were performed in the same solution under open circuit potential during sliding against 10 mm alumina balls. Results showed that plasma-nitrided samples presented better corrosion behaviour in terms of tendency to corrosion, corrosion rate, and polarization resistance, as compared to the other studied surface treatments. Together with nitrocarburised samples, plasma-nitrided samples also exhibited lower tendency to corrosion under sliding.
Keywords: Corrosion; Nitriding; Nitrocarburising; Plastic mould steel; Tribocorrosion